Enhanced isobutanol production from acetate by combinatorial overexpression of acetyl-CoA synthetase and anaplerotic enzymes in engineered Escherichia coli - Song, Hun Suk; Seo, Hyung Min; Jeon, Jong Min; Moon, Yu Mi; Hong, Ju Won; Hong, Yoon Gi; Bhatia, Shashi Kant; Ahn, Jungoh; Lee, Hongweon; Kim, Wooseong; Park, Yong Cheol; Choi, Kwon Young; et al. (Biotechnology and Bioengineering, 2018)
Acetic acid is an abundant material that can be used as a carbon source by microorganisms. Despite its abundance, its toxicity and low energy content make it hard to utilize as a sole carbon source for biochemical production. To increase acetate utilization and isobutanol production with engineered Escherichia coli, the feasibility of utilizing acetate and metabolic engineering was investigated. The expression of acs, pckA, and maeB increased isobutanol production by up to 26%, and the addition of TCA cycle intermediates indicated that the intermediates can enhance isobutanol production. For isobutanol production from acetate, acetate uptake rates and the NADPH pool were not limiting factors compared to glucose as a carbon source. This work represents the first approach to produce isobutanol from acetate with pyruvate flux optimization to extend the applicability of acetate. This technique suggests a strategy for biochemical production utilizing acetate as the sole carbon source.
Keywords: Abundant materials; Acetate; Anaplerotic enzymes; Engineered escherichia coli; Flux optimization; Isobutanol; Over-expression; Sole carbon source; Acetate-CoA Ligase; Acetates; Butanols; Escherichia coli; Gene Expression; Metabolic Engineering; acetate; anaplerotic enzymes; Escherichia coli; isobutanol